SERVANT LEADERSHIP IN THE INDIAN IT SECTOR: AN EMPIRICAL ASSESSMENT OF ORGANIZATIONAL BENEFITS AND OPERATIONAL CHALLENGES (Lex localis - Journal of Local Self-Government, 2025)
This study empirically examines the dual impact of servant leadership within India’s IT sector, analyzing its influence on twelve organizational variables—six representing benefits (e.g., trust, collaboration, employee satisfaction) and six denoting challenges (e.g., decision-making delays, role ambiguity, inefficiency). Based on survey data from 200 professionals across five major IT firms, the findings reveal that servant leadership significantly enhances psychological safety, ethical climate, and team synergy, with over 75% agreement. However, structural drawbacks persist, including blurred authority and slower responsiveness, with mean scores below 3.2. A one-way ANOVA confirms a statistically significant difference (F = 584.82, p < 0.0001) between positive and negative perceptions. The study contributes to leadership theory by quantifying servant leadership’s organizational impact and offers actionable insights for IT managers seeking to balance empowerment with execution.